Integrated Approach to Pediatric bronchiolitis Control: Role of Respiratory Professionals, Nursing Care, Imaging Support, Primary Care, Pharmacotherapy, and Public Health Surveillance - Alamar, Abdullah Mastour; Amwaj Qassem alqahtani; Abduljalil salah Alahmadi; Ahmed Mohammed Masrhi; Mohammad Omar Mohammad Sultan; Ali Mohammed Ali Qaysi; Kheder Moussa Yahia Gabarri; Tariq Ahmed Hamoud Al Khairat; Hana Saeed Faqih (Saudi Journal of Medicine and Public Health, 2025)
Background: Pediatric bronchiolitis is among the most common respiratory illnesses affecting infants, primarily caused by respiratory syncytial virus (RSV), with significant clinical and economic burden during seasonal surges. Aim: To summarize the etiology, epidemiology, clinical features, management strategies, preventive interventions, and complications associated with pediatric bronchiolitis. Methods: A comprehensive review of clinical, epidemiological, and pathophysiological information extracted from recent literature detailing viral causes, risk factors, clinical progression, diagnostic practices, and treatment approaches. Results: Bronchiolitis primarily affects infants aged two to six months and is influenced by host, environmental, and social risk factors such as prematurity, congenital heart disease, tobacco smoke exposure, and overcrowding. Diagnosis remains clinical, while management focuses on hydration, oxygen therapy, secretion clearance, and symptom monitoring. Preventive measures—including maternal RSV vaccination and infant monoclonal antibody administration—significantly reduce hospitalization and severe disease burden. Conclusion: Bronchiolitis is typically self limiting but may progress rapidly in high risk infants. Early recognition, supportive care, and expanded preventive strategies remain essential to reducing morbidity.